Renal angioplasty stenting under embolic protection device: first human study with the FiberNet™ 3D filter. (October 2010) - Henry, Michel; Henry, Isabelle; Polydorou, Antonios; Hugel, Michèle
Background : Atheroemboli are the rule in any intervention and the leading cause of complications during percutaneous coronary intervention, carotid angioplasty (CAS), and probably after renal angioplasty stenting (RAS), which could explain the renal function deterioration after RAS in 20–30% of the cases. Several series of RAS under protection were reported using current embolic protection devices (EPDs), but these EPD have significant limitations that may be addressed by a new EPD, the FiberNet™ (Lumen Biomedical Inc, MN, USA).Methods : FiberNet is a 3D expandable filter made of fibers, which expands radially to fill the lumen, that is mounted onto a 190-cm long 0.014-inch wire. No delivery sheath is required. The crossing profile (1.7–2.9F) is low. With the retrieval catheter a focal suction can be performed during device removal allowing a meticulous cleaning of the vessel. The filter can fill vessels from 1.75 to 7 mm without requiring a long landing zone, allowing protection in the majority of renal arteries. FiberNet can capture particles as small as 40 µm without compromising the flow.Results : After a series of 139 protected renal angioplasties performed with current EPDs, we began the first human study with FiberNet. A total of 12 ostial lesions (R: 6, L: 6) were treated in 12 hypertensive patients (Male: ten). The mean age of patients was 64 years, with an average stenosis of 79%, two patients had moderate renal insufficiency. FiberNet crossed 11 lesions without predilatation (one predilatation was necessary for a subocclusive very calcified ostial lesion). Technical success was observed in 100% of patients with no reported complications. All samples visually contained significant amounts of emboli. The mean debris surface area was 106 mm 2 (aspirated debris: 82 mm 2, debris in the filter: 24 mm 2 ). The mean number of particles 28–60 µm: 2136 ± 776, greater than 60 µm: 5918 ± 1362. At 6-month follow-up, we observed no deterioration of the renal function.Conclusion: The first human use of this new novel EPD in RAS is encouraging. FiberNet was easy to use and it captures particles of 30/40 µm without compromising the flow, which seems to be an improvement in comparison with current EPD. The amount of debris removed is comparable during RAS and CAS. Additional patients will demonstrate the overall performance of this new EPD and its role to preserve the renal function and improve long-term results of RAS.